Assessing resource-use efficiency of land use. (September 2018) - Herzig, Alexander; Nguyen, Trung Thanh; Ausseil, Anne-Gaelle E.; Maharjan, Ganga Ram; Dymond, John R.; Arnhold, Sebastian; Koellner, Thomas; Rutledge, Daniel; Tenhunen, John
Abstract: We introduce an explicit indicator and the Land Use Management Support System to assess the resource-use efficiency of land use (RUE) at the landscape scale. To estimate RUE, we relate land-use performance with regard to ecosystem services indicators to the maximum possible land-use performance based on an optimised land-use configuration. The test application of the RUE assessment in the Haean catchment, South Korea, shows that the land-use system's RUE could be increased by 11% for both nitrate and sediment loss. The estimated headroom could indicate whether potential contaminant reduction targets for the downstream water reservoir Lake Soyang could be achieved with the current land-use system. The recurring RUE assessment for a given region might indicate the effectiveness of spatial planning and policy measures to improve the RUE in that region. Future work should address the integration of RUE into a participatory spatial planning or resource-management framework. Highlights: We introduce an explicit indicator for resource-use efficiency of land use (RUE). We introduce a systematic procedure to facilitate the application of RUE. We introduce the Land-Use Management Support System for assessing RUE. We test the assessment of RUE in the Haean catchment, South Korea. We provide the data set and assessment tool to replicate the analysis in the paper.